The Effect of Tax Awareness, Tax Sanctions, Tax Amnesty and Fiscal Services on Taxpayer Compliance - Eka Rahmawani; Afriyanti Hasanah (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to see whether tax awareness, tax sanctions, tax amnesty, and tax service services had an effect on individual taxpayer compliance at KPP Pratama Batam Utara. This study uses quantitative methods to collect data with SPSS. The sample is 100 active taxpayer respondents and registered at KPP Pratama Batam Utara from 2017 to 2021. The researcher uses the sampling method in selecting the sample and uses the slovin formula to determine the number of samples. The results of this research conclude that tax awareness has an effect on individual taxpayer compliance, while tax sanctions, tax amnesty, and tax service do not affect individual taxpayer compliance.